The Role of Correctional Social Worker on Implementation Diversion Process for Children Facing Legal Issues - Ali Equatora, Muhammad; Imas Yusmiati, Eneng; Fernandes Butar Butar, Herry; Upe, Ambo (International Journal of Psychosocial Rehabilitation, 2020)
This research explored the correctional social worker’s role in the implementation of the children in conflict with the law. As we understand it, the task and function of the community advisors at the correctional hall (BAPAS) includes being able to develop community research, become a person who assists the client (both adults and also children), become a mentor, and become a supervisor of his clients. In this study, the approach used is a qualitative method, with a descriptive approach where the research results will give an accurate picture of the role of the correctional social worker in the implementation of diversion toward children who faced legal issues The Indonesian correctional hall in the year 2019 has successfully implemented a diversion program by performing the motivational interview approach. The results of the research provided an overview of the role of community advisers, where the method of motivational interview techniques conducted by community advisers has made progress on the success of the child diversion. Providing four principles includes holding in curating the attitude of empathy, the development of the disrepair attitudes, developing the approach of the implementation of resistance, and the application of self-efficacy support can be a driver in the success of the child diversion.